«PUBLIC ADMINISTRATION»: PLACE IN THE SYSTEM OF ADMINISTRATIVE LAW - Kunev, Yuriy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article: to determine the essence, content and meaning of the concept of «public administration» and its place among the main administrative and legal concepts. Research methods: systematic analysis and synthesis, knowledge of the theory and practice of administrative law; methods of dialectical and formal logic made it possible to formulate and clarify the concept of public administration, as well as a method of generalization and modeling of new theoretical knowledge. Results: the opinions of scientists on the main reasons for the introduction of the concept of «public administration» into the administrative sphere are presented. The problems of the further development of the theory and system of administrative law for the identification of different concepts «administrative activity» and «public administration» are identified. The main characteristics of public administration, which distinguish it from administrative activity, are given. It was concluded that the introduction of the concept of «public administration» into the theory of administrative law took place and continues to take place without understanding its meaning and content as a subject of administrative law. Public administration is a type of management activity, the purpose of which is the development and adoption of administrative development programs, in particular, administrative activity as executive. Discussion: the position is argued that public administration as a practical management activity is a superstructure over political and administrative activities and should contribute to their development. It is proposed to define public administration as a type of management activity, not executive activity.